2020
DOI: 10.5539/elt.v13n6p118
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Thai EFL Learners’ Ability to Self-correct Errors in Written English Sentences through Games

Abstract: Games have been widely accepted as an effective tool for language learning. They help learners achieve better learning outcome and create a learning atmosphere which contribute to learners’ learning. The present study, hence, employed games to help EFL learners write better in English. In the present study, games were used to encourage Thai EFL learners to self-correct errors found in their English sentences. After five weeks of learning with games, the learners’ ability to self-correct err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(14 reference statements)
3
1
0
1
Order By: Relevance
“…The results showed that situation-based learning had positive effects on students' sentence writing ability. These results were in agreement with those of [4,9,11,25,28] that situation-based learning was one of the most effective methods that helps strengthen both cognitive and affective abilities of students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that situation-based learning had positive effects on students' sentence writing ability. These results were in agreement with those of [4,9,11,25,28] that situation-based learning was one of the most effective methods that helps strengthen both cognitive and affective abilities of students.…”
Section: Discussionsupporting
confidence: 90%
“…These results supported the study of [28] that situation-based learning provided opportunities for students to focus on meaning in context to help students develop their language usage in a language-rich environment that provided functional meaning for their sentence writing. Besides, the results indicated that students learned new words or vocabularies in various situations which was in agreement with those of [15,18,25] that situation-based learning required cognitive operations which helped students understand unfamiliar words and phrases in various contexts. Students extracted the meaning of new words in different contexts and applied vocabulary knowledge into various contexts.…”
Section: Functionssupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, some of the game-based activities involved recognizing appropriate transitions in a paragraph and demonstrating awareness of essay organization. As Sermsook et al (2020) acknowledged, the use of games encourages learners to develop their writing skills in English by generating enjoyable learning environments, thus ensuring that students become involved in their own learning. Regarding the implementation of gamification to improve the knowledge of grammar and vocabulary, 86.95% of the participants agreed that Genially games helped them improve their grammar, whereas 91.3% mentioned that these activities helped them enhance their knowledge of vocabulary.…”
Section: Resultsmentioning
confidence: 99%
“…En este sentido, el 100% de ellos se mostró totalmente interesado en continuar utilizando este tipo de juegos en su formación profesional como futuros docentes de inglés como lengua extranjera. Al respecto, Sermsook et al, (2020) mencionan que el uso de juegos motiva a los estudiantes durante el desarrollo de la destreza de escribir en inglés debido a que genera ambientes de aprendizaje mucho más placenteros y participativos.…”
Section: Resultados Académicosunclassified